Urea-thiazole/benzothiazole hybrids with a triazole linker: synthesis, antimicrobial potential, pharmacokinetic profile and in silico mechanistic studies - Poonia N.; Lal K.; Kumar A.; Kumar A.; Sahu S.; Baidya A.T.K.; Kumar R. (My University, 2025)
Some urea-thiazole/benzothiazole hybrids with a triazole linker were synthesized via Cu(I)-catalysed click reaction. After successfully analysed by various spectral techniques including FTIR, NMR and HRMS, antimicrobial screening of the synthesized hybrids along with their precursors was carried out against two Gram (+) bacteria (Staphylococcus aureus and Bacillus endophyticus), two Gram (−) bacteria (Escherichia coli and Pseudomonas fluorescens) and two fungi (Candida albicans and Rhizopus oryzae). All the synthesized compounds (4a–4l) displayed better biological response than the standard fluconazole against both of the tested fungi. Compounds 4h and 4j were found to be the most active compounds against R. oryzae and C. albicans, respectively. Molecular docking of hybrid 4j and its alkyne precursor 1b in the active site of C. albicans target sterol 14-α demethylase was also performed and was also supported by molecular dynamics studies. In silico ADME prediction of synthesized urea-thiazole/benzothiazole hybrids with a triazole linker and their alkyne precursors was also predicted. Graphic abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.